An Analysis of English Teachers’ Oral Feedback in Teaching and Learning Process - Mulyadin, Asrul (Gayaku Publisher, 2024)
This research aims to analyze the types of oral feedback of the English teachers in the teaching and learning process and the reasons for the teachers in giving oral feedback in the learning process. This research is descriptive. In collecting the data, the teachers were observed and video and audio recording came as tools. To investigate the reason of the teachers, the data collected use Stimulated Recall Interview (SRI). The findings of the research, there are 6 sub-types of oral feedback used by the teachers that are recast, elicitation, clarification request, commenting, repetition, and praise. The second finding about reasons for teacher in giving oral feedback are oral feedback is needed in the class, the teachers’ attention to the students, the teachers want to correct the students’ mistake and their performance, keeping the interaction with the students, motivating the students and appreciating the students’ performance.